Immunotherapy of systemic sclerosis - Christina G. Katsiari; Theodora Simopoulou; Ioannis Alexiou; Lazaros I. Sakkas (Human Vaccines & Immunotherapeutics, 2018)
Systemic sclerosis (SSc) is a chronic systemic disease characterized by microvasculopathy, immune activation, and extensive collagen deposition. Microvasculopathy and immune activation occur very early in the disease process. Evidence from animal models and in vitro studies indicate that T-cells and B-cells activate fibroblasts to produce collagen. Traditional immunosuppressants, cyclophosphamide(CyP), methotrexate(MTX), and more recently mycophenolate mofetil(MMF), may prove more effective if used very early in the disease course. These drugs showed some benefit in skin (MTX, CyP, MMF) and lung function (CyP, MMF). Biologicals, such as intravenous immunoglobulin (IVIg), belimumab(Beli), tocilizumab(TCZ), abatacept(Aba), rituximab(RTX) and fresolimumab(Fresu) appear promising as they exhibited some benefit in skin (IVIg, Beli, TCZ, Aba, RTX, Fresu), hand function (IVIg), and joints (IVIg, TCZ, Aba). Autologous stem cell transplantation showed the best therapeutic efficacy on skin and internal organs, and looks very promising, as modification of transplantation immunosuppression is decreasing the early high mortality.